Exploring relationships between the residential neighbourhood environment and well-being outcomes in New Zealand residing older adults : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Hall, Kelly (Massey University, 2021)
As New Zealand’s population continues to age, we face the increasing challenge of supporting our older adults to live well for longer. Non-communicable diseases have taken over from infectious diseases as the leading cause of mortality, leaving much of our older population living longer with increased health concerns. Amid rising inequality and as the pressure on our health system rises, the health field turns its attention to the social determinants of health for the answer. Environmental influences on well-being have garnered particular attention in recent years. Older adults are theorised to be more susceptible to the neighbourhood environment as functional ability decreases. However, there have been inconsistencies in the research regarding objective and subjective measures of the neighbourhood. This study addresses two objectives; to determine the relationships between objective and subjective measures of the neighbourhood and to test the hypothesis that older adults who reside in more desirable neighbourhoods report higher levels of well-being. The study comprises two population samples; the first comprises 4351 New Zealand residing adults aged 55-92 years old, the second consists of a subgroup of 60 participants aged from 55-82. Bivariate correlations and multiple regression analysis were used to evaluate the data. The study found Natural Elements (trees, public grass, and sounds of nature) and objective measures of the environment to be the most strongly associated with positive perceptions of Neighbourhood Quality. Perceived Neighbourhood Quality, but not objective neighbourhood features, were predictive of well-being outcomes as measured by Loneliness, Depression, and Anxiety in older adults. The study was limited by the low availability of objective assessments and corresponding subjective assessments and the unknown impact of the Covid-19 pandemic. While causality cannot be claimed, the study found evidence of relationships between Neighbourhood perceptions and well-being in older adults.
Keywords: healthy ageing; older adult well-being; neighbourhoods; loneliness; depression; anxiety; 520106 Psychology of ageing